Von Mises stresses on Mushroom-loop archwires for incisor retraction: a numerical study - Marcelo do Amaral Ferreira; Fábio Rodrigo Mandello Rodrigues; Marco Antônio Luersen; Paulo César Borges; Ravindra Nanda; Marcio Rodrigues de Almeida (Dental Press Editora, 2020)
ABSTRACT Objective: To perform a numerical simulation using FEM to study the von Mises stresses on Mushroom archwires. Methods: Mushroom archwires made of titanium-molybdenum alloy with 0.017 x 0.025-in cross-section were used in this study. A YS of 1240 MPa and a Young's modulus of 69 GPa were adopted. The archwire was modeled in Autodesk Inventor software and its behavior was simulated using the finite element code Ansys Workbench (Swanson Analysis Systems, Houston, Pennsylvania, USA). A large displacement simulation was used for non-linear analysis. The archwires were deformed in their extremities with 0° and 45°, and activated by their vertical extremities separated at 4.0 or 5.0 mm. Results: Tensions revealed a maximum of 1158 MPa at the whole part of the loop at 5.0mm of activation, except in a very small area situated at the top of the loop, in which a maximum of 1324 Mpa was found. Conclusions: Mushroom loops are capable to produce tension levels in an elastic range and could be safely activated up to 5.0mm.